The synergistic interaction of thermal stress coupled with overstocking strongly modulates the transcriptomic activity and immune capacity of rainbow trout (Oncorhynchus mykiss) - Rebl, Alexander; Korytář, Tomáš; Borchel, Andreas; Bochert, Ralf; Strzelczyk, Joanna Ewa; Goldammer, Tom; Verleih, Marieke (Scientific reports, 2020)
The objective of the present study is to identify and evaluate informative indicators for the welfare of rainbow trout exposed to (A) a water temperature of 27 °C and (B) a stocking density of 100 kg/m3 combined with a temperature of 27 °C. The spleen-somatic and condition index, haematocrit and the concentrations of haemoglobin, plasma cortisol and glucose revealed non-significant differences between the two stress groups and the reference group 8 days after the onset of the experiments. The transcript abundance of almost 1,500 genes was modulated at least twofold in in the spleen of rainbow trout exposed to a critical temperature alone or a critical temperature combined with crowding as compared to the reference fish. The number of differentially expressed genes was four times higher in trout that were simultaneously challenged with high temperature and crowding, compared to trout challenged with high temperature alone. Based on these sets of differentially expressed genes, we identified unique and common tissue- and stress type-specific pathways. Furthermore, our subsequent immunologic analyses revealed reduced bactericidal and inflammatory activity and a significantly altered blood-cell composition in challenged versus non-challenged rainbow trout. Altogether, our data demonstrate that heat and overstocking exert synergistic effects on the rainbow trout's physiology, especially on the immune system.
Keywords: nahuštění v prostoru; Animals; imunitní systém; Heat-Shock Response; slezina; Immune System; Crowding; hydrokortison; Hydrocortisone; stanovení celkové genové exprese; rybí proteiny; Computational Biology; Hemoglobins; glukosa; Glucose; Fish Proteins; Spleen; reakce na tepelný šok; hemoglobiny; transkriptom; Oncorhynchus mykiss; zvířata; Transcriptome; výpočetní biologie; Gene Expression Profiling